Knowing and Using 4-H Curricula - Marilyn N. Norman; Joy C. Jordan (EDIS)
In planning experiences for youth that target life skills and help youth become aware of the concepts they have learned from those experiences, it is important to remember that young people have different learning styles, and approach or respond to a learning activity differently. Adults will have the most success in appealing to youth if there are a wide variety of activities with opportunities for all learning styles. This document is 4HS FS101.8, one of a series of the 4-H Youth Development Department, UF/IFAS Extension. Published May 2006.